Improved Fastener-Based Modelling Method for Reinforced Cold-Formed Steel Shear Walls - Xingxing Wang; Youcheng Li; Wei Wang; Shangxin Gao (Advances in Civil Engineering)
The fastener-based computational model is improved and extended to predict the shear performance of reinforced cold-formed steel (RCFS) shear walls. The failure mechanism of sheathing-to-stud connections with double-layer wallboards is first analysed, and a method for determining those connections’ shear properties is proposed. Numerical models of RCFS shear walls are then established and analysed. Based on simulated results that have been fully validated by previous test results, an equivalent method for perforated RCFS shear walls is proposed. Finally, the application of the improved fastener-based modelling method to mid-rise RCFS shear walls is verified. The following results were obtained. (1) The simulated load-displacement curves can fully reflect shear wall hysteretic characteristics; moreover, the relative errors between the simulated and test results are within 14.2%. (2) The equivalent method that simplifies the wall segment over an opening as a linear elastic beam is applicable in the case of 1.5 < b/d (i.e., the ratio of the opening width to the depth of the wall segment over the opening) ≤5.0. (3) The improved fastener-based modelling method can be used to effectively predict the lateral performance of mid-rise RCFS shear walls.